The healthy eating index may not be an appropriate indicator for assessing dietary quality in breast cancer survivors: results from NHANES 2005–2018 - Zheng, Hao; Chen, Siyang; Huang, Lihua; Zhou, Xiao; Huang, Qingxi; Li, Xuemei; Zhao, Yanli (Frontiers in Nutrition, 2024)
BackgroundEvidence on the relationship between the Healthy Eating Index (HEI) and mortality in breast cancer (BC) survivors remains inconclusive. Moreover, rare studies have explored the effect of individual HEI components on survival in this population. This study explored the association between the HEI-2020, including total and 13 component scores, and mortality in BC survivors.MethodsThis cross-sectional study included data of 481 female BC survivors (representing a 3.3 million population) obtained from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. The HEI-2020 total and component scores (higher scores indicating superior dietary quality) were calculated based on the 24 h dietary recall interview. Data on mortality until December 31, 2019, were obtained from the NHANES Public-Use Linked Mortality File. The weighted Cox proportional hazards models were used to assess the association between HEI-2020 and mortality outcomes.ResultsAfter fully adjusting for confounders, a qualified total HEI-2020 score (≥60) was significantly associated with reduced non-cancer mortality (HR 0.59, 95%CI: 0.35–0.99), but not with all-cause or cancer-specific mortality. Among the 13 HEI components, a lower intake of added sugars (with a qualified component score) was linked to a decreased risk of both all-cause and non-cancer mortality (HR 0.44 and 0.25, 95%CI: 0.25–0.77 and 0.13–0.48, respectively, all p < 0.05). Conversely, higher consumption of seafood and plant proteins (with a qualified component score) correlated with an increased risk of cancer-specific mortality (HR 3.64, 95%CI: 1.57–8.45), and a higher intake of dairy was associated with an elevated risk of both all-cause and non-cancer mortality (HR 2.12 and 2.81, 95%CI: 1.36–3.29 and 1.56–5.07, respectively).ConclusionHigher total and component scores of the HEI-2020 do not uniformly confer a lower mortality risk for BC survivors. The HEI-2020 may not be an appropriate indicator for post-diagnosis dietary assessment or recommendations for BC survivors.